Impact of gold and oil prices on the stock market in Pakistan - Aiza Shabbir; Shazia Kousar; Syeda Azra Batool (Journal of Economics, Finance and Administrative Science, 2020)
Purpose - The purpose of the study is to find out the impact of gold and oil prices on the stock market. Design/methodology/approach - This study uses the data on gold prices, stock exchange and oil prices for the period 1991-2016. This study applied descriptive statistics, augmented Dickey-Fuller test, correlation and autoregressive distributed lag test. Findings - The data analysis results showed that gold and oil prices have a significant impact on the stock market. Research limitations/implications - Following empirical evidence of this study, the authors recommend that investors should invest in gold because the main reason is that hike in inflation reduces the real value of money, and people seek to invest in alternative investment avenues like gold to preserve the value of their assets and earn additional returns. This suggests that investment in gold can be used as a tool to decline inflation pressure to a sustainable level. This study was restricted to use small sample data owing to the availability of data from 1991 to 2017 and could not use structural break unit root tests with two structural break and structural break cointegration approach, as these tests require high-frequency data set. Originality/value - This study provides information to the investors who want to get the benefit of diversification by investing in gold, oil and stock market. In the current era, gold prices and oil prices are fluctuating day by day, and investors think that stock returns may or may not be affected by these fluctuations. This study is unique because it focusses on current issues and takes the current data in this research to help investment institutions or portfolio managers.
Keywords: 330; Gold prices; Oil prices; Stock market